426=(x*3)+96

Simple and best practice solution for 426=(x*3)+96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 426=(x*3)+96 equation:



426=(x*3)+96
We move all terms to the left:
426-((x*3)+96)=0
We add all the numbers together, and all the variables
-((+x*3)+96)+426=0
We calculate terms in parentheses: -((+x*3)+96), so:
(+x*3)+96
We get rid of parentheses
x*3+96
Wy multiply elements
3x+96
Back to the equation:
-(3x+96)
We get rid of parentheses
-3x-96+426=0
We add all the numbers together, and all the variables
-3x+330=0
We move all terms containing x to the left, all other terms to the right
-3x=-330
x=-330/-3
x=+110

See similar equations:

| 5x^2-10x-35=0 | | 18=g=6 | | 10^x=83 | | 10^x=983 | | N^2+5h=160 | | -3(n+6)=6 | | 1/3x=2x-45 | | 2w^2-8w-24=0 | | +3+-2=a | | 21m=9 | | 1.4x+6x=3 | | 311=(x*8)+7 | | 4=-4+x/2 | | 1094=(x*2)+4 | | 140=(x-2)180÷x | | 4x-6x=-2x+-5 | | 6x+9=16-x | | 140=(n-2)180÷n | | 10x=x^2-11 | | 7m+3(m+2)=-21 | | x-19=5-3x | | 288=-8(6x+5)-8 | | 4(2x-3)-1=-7 | | 12b-7=29 | | 4^4x-3=4^8-9x | | x-19=5x+16 | | 2x=x/3-45 | | 1.5d+9.75d=1+3.25d | | 2x=45-(x/3) | | 4/4=n/6 | | x+x+x+6=78 | | 4=8q-6q |

Equations solver categories